Analisis Perilaku dan Kinerja Pasar serta Alternatif Kebijakan Pengembangan Sapi Potong di Kabupaten Aceh Besar - Jamilah - (Jurusan Manajemen Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2012)
This research is purposed to analyz conduct and performance market of beef cattle in Aceh Besar regency so will can an konfrehensive explain rate of efficiency of marketing of beef cattle. To observe alternative of developing program of beef who can to apply in Aceh Besar regency. Metods of research is survey metods. If the track marketing is shotter, the price of marketing will be smaller spent, more bigger marketing margin, price share will be bigger and exceptionally to the trade. The collution between from seller is strong. Price competitive on rate seriously. Benefit of marketing is influenced by added of beef cattle, cost of marketing, and metods of selling of seller. The distribution of price share not fair so marketing system be not effecien. The developing of Aceh beef cattle must be developing of regency agribusiness berbasis beef cattle in Aceh Besar regency is integrited of beef cattle developing, organic of agriculture, raising of agroindustries and business developing of beef cattle.Keywords: Beef cattle, conduct n performance market.